EFFECT OF ZINK TABLETS INTERVENTION IN ZINC DEFICIENCY OF TRIMESTER III PREGNANT WOMEN TOWARD WEIGHT AND BODY LENGTH OF NEWBORN - Nurfadillah S; Wardihan Sinrang; Suryani As'ad; Muh. Nasrum Massi; Mardiana Ahmad; Nilawati Usman (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: According to 2018 World Health Organization (WHO) data globally, an estimated 17.3% of the population has inadequate zinc intake, with estimates ranging from 5.7% in Oceania to 7.6% in Europe, 9.6% in America and the Caribbean, highest in Africa (23.9%) and Asia (19.6%). Zinc is important for the function of a number of enzymes and growth hormones during pregnancy. In pregnant women, the relative zinc concentration decreases up to 35% due to the influence of hormonal changes and the transport of nutrients from mother to baby. Objectives: The purpose of this study was to identify the effect of giving zinc tablets to pregnant women with zinc deficiency in the third trimester on body weight and length of babies born at the Makassar City Health Center. Methods: This type of research is True Experimental with a pretest-posttest design with a control group. The sample in this study was 62 samples of third trimester pregnant women, and the sampling technique used was purposive sampling. Measurement of zinc levels in third trimester pregnant women using the Elisa reader kit at the Research Laboratory of the Hasanuddin University Teaching Hospital. The research instruments were in the form of a research explanation sheet, respondent's consent sheet, respondent's checklist sheet, and the mother's zinc tablet consumption control sheet for 14 days. Results: Judging from the average value of newborns in pregnant women who did not have zinc deficiency, the average value of birth weight in pregnant women with zinc deficiency was 15.70 g/dL and 18.95 g/dL. zinc deficiency with a value (p < 0.05), while pregnant women with zinc deficiency have an average birth length of 10.00 g/dL and mothers who do not have a deficiency of 19.87 g/dL with a value (p < 0.05). So, it can be concluded that giving zinc tablets to pregnant women in the third trimester has an effect on Birth Weight (BBL) and Birth Length (PBL). Conclusion: Giving zinc tablets has an effect on increasing zinc levels in third trimester zinc deficiency pregnant women and increasing birth weight and length of the baby.